"Who really killed cock robin": aesthetic meaning making in preservice teacher training. (3rd April 2018) - Upshaw, Allison
ABSTRACT: This storied account details a reflective inquiry of dance as an instructional tool in a preservice teacher training program. The case study follows a children's literature class as they use movement/dance as a way of making meaning in teacher selected literature. Student teachers learned basic movement concepts through BEST (Body, Energy, Space, Time). Following the Kennedy Center definition of arts integration, the participants examined how dance/movement could be used to make meaning in a literary context. They were taken step by step through one way of integrating movement/dance and text, and then led a small of groups of fifth graders through the same or similar process. Through an examination of their responses to journal prompts, and classroom discussions, this article highlights the journey of understanding embarked upon by both the researcher and the participants.